Proceedings of the IEEE 27th Annual Northeast Bioengineering Conference (Cat. No.01CH37201)
DOI: 10.1109/nebc.2001.924694
|View full text |Cite
|
Sign up to set email alerts
|

Polymer nanofiber thin films for biosensor applications

Abstract: In this paper a nanofiber (NF) thin film is proposed as a new sensing interface for chemical and biochemical sensor applications. NFs made of Poly-Lactic Acid-Co-Glycolic Acid (PLAGA) polymer with the diameters about SO0 nm were deposited on the gold surface of a thickness shear mode (TSM) micro viscoelastic sensor operating at 10 MHz. The NF thin film coated TSM sensors exposed to gaseous and liquid media under various ambient conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 1 publication
0
6
0
1
Order By: Relevance
“…The associate editor coordinating the review of this paper and approving it for publication was Dr. Richard Fair. chemical warfare agents, and biological species [1]- [4]. They are used mostly to detect the adsorption or attachment of protein molecules [5], cells [6], bacteria [7], or the immunological properties of cytokines conjugated to organisms on the plate surface of two-port IDTs [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The associate editor coordinating the review of this paper and approving it for publication was Dr. Richard Fair. chemical warfare agents, and biological species [1]- [4]. They are used mostly to detect the adsorption or attachment of protein molecules [5], cells [6], bacteria [7], or the immunological properties of cytokines conjugated to organisms on the plate surface of two-port IDTs [8].…”
Section: Introductionmentioning
confidence: 99%
“…There has been a notable development in biosensing detections in recent years, such as the quartz crystal microbalance (QCM) [9], [10], the thickness shear mode (TSM) [1], the acoustic plate mode (APM) [11], the flexural plate wave (FPW) [12]- [16], the love mode [17], the shear horizontal acoustic plate mode (SH-APM) [18], and the surface acoustic wave (SAW) [19]. In general, the FPW has a higher sensitivity with the loading changes at lower operating frequencies among all these detecting methods [20], [21].…”
Section: Introductionmentioning
confidence: 99%
“…Fiber diameter and pore size are the two key factors that affect the performance of the fiber mat. [29][30][31][32][33] By correlating fiber diameter with pore size, we found that the effects of sonic vibration treatment on fiber diameter and pore size follow different tendencies, as shown in Figure 5. Sonic vibration has stronger effects on both the fiber diameter and the pore size.…”
Section: Effect On Pore Structurementioning
confidence: 99%
“…Poly-Lactic Acid-co-Glycolic Acid nanofibers have been deposited on thickness shear mode piezoelectric sensors [72,73]. Feng et al have developed a formaldehyde sensor using a molecularly imprinted polymer as the recognition element and QCM as the sensor [74].…”
Section: Polymer-based Sensorsmentioning
confidence: 99%